Teachers’ and Parents’ Roles in Addressing Learning Difficulties of Students with Autism - Rosmida, Rosmida; Immawati, Sri; Hapiz, Hapiz (Jurnal Prima Edukasia, 2025)
This study aims to describe the roles of teachers and parents in overcoming the learning difficulties of autistic students at Muara Bungo Special Elementary School. A qualitative case study design was employed involving the school principal, classroom teachers, parents, and second-grade students with autism. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using the Miles and Huberman interactive model, including data reduction, display, and verification. Triangulation techniques were applied to ensure credibility and validity. The findings reveal four interconnected factors that contribute to reducing learning difficulties: teachers' adaptive instructional practices, active parental involvement at home, supportive school facilities, and the implementation of Individualised Learning Programs (ILP). Teachers applied multisensory and visual-based strategies, structured routines, and positive reinforcement, which improved students’ attention, participation, and comprehension. Parents supported learning through consistent guidance, home routines, and emotional encouragement, promoting continuity between school and home. Sensory-friendly facilities and assistive technologies enhanced students’ emotional regulation and engagement, while ILPs enabled personalized academic and social development. Thesynergy among teachers, parents, and school resources was found to be essential for addressing students’ diverse needs. These results imply that strengthening teacher–parent collaboration, providing professional training, and optimizing individualized and resource-based support systems are critical for improving educational outcomes for autistic students in special and inclusive elementary settings.